A robust measure of relative informational efficiency for the Malaysian stock market - Lim, Kian Ping; Ling, Tai Hu; Chang, Kwok Boon (Universiti Malaysia Sabah, 2010)
This section provides a brief report for the FRGS project (FRG0283-SS-2/2010), outlining the research problems, research objectives, contributions, data collection, methodology, key findings, policy implications, project output and the organization of this final report.